Preparation method of lanthanum-doped bismuth ferrite film system material
Through the preparation method of the lanthanum-doped bismuth ferrate film system material, the oxygen vacancy and conductivity are adjusted by using solvent gel method and pulse laser deposition method, and the problem of lattice defects in BiFeO3 film affecting physical properties is solved, and the growth and conductivity of high-quality films are achieved.
Patent Information
- Application Number
- CN202510087651.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lattice defects (such as oxygen vacancies of ions) in BiFeO3 films affect their physical properties, and it is difficult for the prior art to effectively adjust oxygen vacancies and conductivity.
The preparation method of lanthanum-doped bismuth ferrate film system material is adopted, and the components are mixed at the molecular level by solvent gel method, and the film is grown by pulsed laser deposition method, and the lanthanum doping ratio is adjusted to introduce oxygen vacant at different concentrations.
It realizes effective adjustment of oxygen vacancies and conductivity, improves the crystallinity and phase purity of the film, enhances the conductivity, and is suitable for information storage, mobile communications and electronic devices.
Smart Images

Figure CN119841668A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic functional thin film materials and relates to a method for preparing a lanthanum-doped bismuth ferrite thin film system material. Background Art
[0002] In recent years, ferroelectric materials have shown more and more broad application prospects in the fields of ferroelectric storage, photocatalytic degradation, high-temperature piezoelectric devices, energy storage dielectrics and ferroelectric photovoltaics due to their advantages such as non-volatile storage, high-speed operation, low energy consumption, excellent electrical properties, temperature stability, strong adaptability and structural adjustability. Thin film materials with excellent ferroelectric and piezoelectric properties have become one of the hot spots in the current research field. Bismuth ferrite (BiFeO3) has become a type of lead-free and environmentally friendly material comparable to lead-based materials due to its room temperature multiferroic properties (ferroelectric Curie temperature is 1103K and antiferromagnetic Neel temperature is 643K), providing great application possibilities for the development of new information storage and processing and magnetoelectric devices based on ferroelectric-magnetic integrated effects. However, lattice defects in BiFeO3 films (such as oxygen vacancies of ions) have received widespread attention because their presence can affect physical properties such as electron transport, magnetism and ferroelectricity. We used electric field to regulate the Bi 1-x La x The conductive state of FeO3 film. The addition of trivalent lanthanum ions can regulate oxygen vacancies and maintain Fe 3+ The phase structure, oxygen vacancy concentration and film conductivity can be adjusted by controlling the doping ratio. Summary of the invention
[0003] In view of the above problems, the present invention provides a lanthanum-doped bismuth ferrite film capable of adjusting oxygen vacancies and conductivity and a preparation method thereof.
[0004] The method for preparing the lanthanum-doped bismuth ferrite thin film system material of the present invention specifically comprises the following steps:
[0005] (1) Lanthanum nitrate tetrahydrate, bismuth nitrate pentahydrate and iron nitrate nonahydrate were mixed by 1-x La x Weigh the chemical molar ratio of FeO3 element, then weigh citric acid, dissolve the weighed mixture in a mixed solvent beaker of methanol and ethylene glycol, put a magnetic stirrer in the beaker, put the beaker on a constant temperature magnetic uniform table for uniform stirring, control the magnetic speed, and get a uniform solution after a period of time;
[0006] (2) moving the uniform solution of step (1) to a heated magnetic uniform table for stirring and heating for a period of time, and when the solvent evaporates to form a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a gel, taking the gel out of the beaker, and putting it into a pre-cleaned mortar to fully grind it to obtain a lanthanum-doped bismuth ferrite ceramic powder, and placing the lanthanum-doped bismuth ferrite ceramic powder into a box furnace for pre-sintering treatment, controlling the heating rate, initial sintering time, and sintering temperature to obtain a primary calcined powder;
[0007] (3) placing the primary calcined powder in step (2) into a specific mold and subjecting it to pressure treatment to prepare a lanthanum-doped bismuth ferrite ceramic block, and placing the obtained ceramic block into a box-type furnace for calcination to obtain a lanthanum-doped bismuth ferrite ceramic target;
[0008] (4) The bulk target was deposited on a LaAlO3 substrate using pulsed laser deposition to obtain Bi 1-x La x FeO3 thin film.
[0009] In the step (1) of the present invention, x=0.05-0.30, the molar ratio of citric acid to the metal cation of lanthanum-doped bismuth ferrite is 1:1, the volume ratio of methanol to ethylene glycol is 5:1-3:1, the stirring time is 30-60 minutes, and the magnetic speed is 200-400 r / min.
[0010] In step (2) of the present invention, the heating temperature of the mixed solution is 80-100°C, the heating time is 0.5-2h, the oven drying temperature is 50-100°C, the drying time is 12-24h, the grinding time is 0.5-1h, the heating rate is 2-4°C / min, the initial sintering temperature is 400-600°C, the initial sintering time is 2-4h, and the sintering conditions are normal pressure and air atmosphere.
[0011] In step (3) of the present invention, the pressure of the tablet press is 1-2Mpa, the pressurization time is 20-30min, the calcination temperature is 700-900°C, the heating time is 2-12h, and the sintering conditions are normal pressure and air atmosphere.
[0012] In step (4) of the present invention, the LaAlO3 substrate is fixed on a suitable position of the liner, and when the vacuum degree of the chamber reaches 1×10 -4 ~2×10 -4 Pa, set the frequency of the pulsed laser to 3-5 Hz, the energy to 200-350 mJ. First grow a bottom electrode, set the heating temperature to 600-700 ° C, the oxygen pressure to 10-30 Pa, and grow Bi 1-x La x After the FeO3 film is grown, 1×10 4 ~5×10 4Pa oxygen annealing, annealing time 45 ~ 60min, get Bi 1-x La x FeO3 thin film.
[0013] Beneficial effects of the present invention:
[0014] The purpose of the present invention is to provide a method for preparing a lanthanum-doped bismuth ferrite thin film system material. The present invention adopts a solvent gel method to ensure the mixing of various components at the molecular level, and the epitaxially grown film has good quality, good crystallinity, and high phase purity. The method is simple in process, good in repeatability, and the selected chemical reagents are inexpensive and easy to obtain, with a high yield rate, and Bi 1-x La x Atomic-level flat morphology, good hysteresis loop and butterfly curve were observed in the FeO3 system thin film samples. By adjusting the lanthanum doping ratio to introduce different concentrations of oxygen vacancies, the conductivity of the film was enhanced. It is expected to be used in information storage, mobile communications, electronic devices and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Example 1Bi 1-X Ca X XRD pattern of FeO3 (where x = 0.05-0.30) thin film system material;
[0016] Figure 2 Example 1Bi 1-X La X SEM images of FeO3 (x=0, 0.10, 0.30) targets;
[0017] Figure 3 Example 1Bi 0.95 La 0.05 AFM morphology of FeO3 thin film system materials;
[0018] Figure 4 Example 1Bi 0.95 La 0.05 IV curve of FeO3 thin film system materials;
[0019] Figure 5 Example 2Bi 0.95 La 0.05 Hysteresis loop and butterfly curve of FeO3 thin film system materials;
[0020] Figure 6 Example 2Bi 0.90 La 0.10 AFM morphology of FeO3 thin film system materials;
[0021] Figure 7 Example 2Bi 0.90La 0.10 IV curve of FeO3 thin film system materials;
[0022] Figure 8 For comparative example 1Bi 0.90 Ca 0.10 Hysteresis loop and butterfly curve of FeO3 thin film system materials;
[0023] Fig. 9 For comparative example 1Bi 0.80 La 0.20 AFM morphology of FeO3 thin film system materials;
[0024] Fig.10 For comparative example 1Bi 0.80 La 0.20 IV curve of FeO3 thin film system materials;
[0025] Fig.11 For comparative example 1Bi 0.80 La 0.20 Hysteresis loop and butterfly curve of FeO3 thin film system materials;
[0026] Fig.12 For comparative example 2Bi 0.70 La 0.30 AFM morphology of FeO3 thin film system materials;
[0027] Fig.13 For comparative example 2Bi 0.70 La 0.30 IV curve of FeO3 thin film system materials;
[0028] Fig.14 For comparative example 2Bi 0.70 La 0.30 Hysteresis loop and butterfly curve of FeO3 thin film system materials. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the described contents.
[0030] Example 1
[0031] (1) Lanthanum nitrate tetrahydrate, bismuth nitrate pentahydrate and iron nitrate nonahydrate were mixed by 1-x La xThe FeO3 element chemical molar ratio is weighed, x=0.05, and then citric acid is weighed. The weighed mixture is dissolved in a mixed solvent beaker of methanol and ethylene glycol, and the volume ratio of methanol to ethylene glycol is 3:1. A magnetic stirring bar is placed in the beaker, and the beaker is placed on a constant temperature magnetic uniform table for uniform stirring. The magnetic speed is controlled, and a uniform solution is obtained after a period of time. The stirring time is 30 minutes, and the magnetic speed is 200r / min;
[0032] (2) moving the uniform solution of step (1) to a heated magnetic uniform table for stirring and heating for a period of time, the heating temperature is 80°C, the heating time is 0.5h, and the solvent evaporates to form a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a gel, the oven drying temperature is 100°C, the drying time is 24h, taking the gel out of the beaker, putting it into a pre-cleaned mortar and grinding it thoroughly, the grinding time is 0.5h, and obtaining a lanthanum-doped bismuth ferrite ceramic powder, placing the lanthanum-doped bismuth ferrite ceramic powder into a box furnace for pre-sintering treatment, the heating rate is 2°C / min, the initial sintering temperature is 500°C, the initial sintering time is 2h, the sintering conditions are normal pressure and air atmosphere, and obtaining a primary calcined powder;
[0033] (3) placing the primary calcined powder in step (2) into a circular mold and subjecting it to a pressurizing treatment, wherein the pressure of the tablet press is 1 to 2 MPa and the pressurizing time is 20 min, to prepare a lanthanum-doped bismuth ferrite ceramic block, and placing the obtained ceramic block into a box-type furnace for calcining, wherein the calcining temperature is 900° C., the heating time is 2 h, and the sintering conditions are normal pressure and air atmosphere, to obtain a lanthanum-doped bismuth ferrite ceramic target;
[0034] (4) Bi 0.95 La 0.05 The FeO3 target material is sanded and then cleaned with alcohol and dust-free paper. The LaAlO3 substrate is placed in a box furnace and sintered at 1000℃ for 2h. The sintering conditions are normal pressure and air atmosphere. The LaAlO3 substrate is fixed to the appropriate position of the liner with silver paste, the silver paste is dried, and the target material is placed in the appropriate position of the target position. The cavity is first vacuumed and pre-sputtered. After sputtering, a layer of La is grown first. 0.5 Sr 0.5 MnO3 bottom electrode, set the cavity infrared laser heating temperature to 700℃, after growing the bottom electrode, grow Bi 0.95 La 0.05 FeO3 film, set the cavity infrared laser heating temperature to 660℃, after growth, perform oxygen annealing, cool down to obtain Bi 0.05 La 0.15 FeO3 thin film.
[0035] The Bi prepared in this example 1-X Ca XXRD of FeO3 (where x = 0.05-0.30) thin film system materials Figure 1 As shown, it can be seen that the phase is a mixed phase.
[0036] The Bi prepared in this example 1-X La X SEM images of FeO3 (x = 0, 0.10, 0.30) targets Figure 2 As shown in the figure, it can be seen that after BFO is doped with La, when the doping concentration is 0.10, due to the influence of lattice distortion and charge compensation mechanism, many voids and uneven grain size distribution are shown in the SEM image. As the doping concentration increases to 0.30, the lattice adjustment reduces the number of voids and the grain size distribution becomes more uniform.
[0037] The Bi prepared in this example 0.95 La 0.05 The morphology of FeO3 film is shown in Figure 3 As shown, it can be seen that the film grows in an island shape.
[0038] The Bi prepared in this example 0.95 La 0.05 The IV curve of FeO3 film is shown in Figure 4 As shown, good conductivity can be seen.
[0039] The Bi prepared in this example 0.95 La 0.05 The hysteresis loop and butterfly curve of FeO3 film are shown in Figure 2. Figure 5 As shown, good hysteresis loop and butterfly curve can be seen.
[0040] Example 2
[0041] (1) Lanthanum nitrate tetrahydrate, bismuth nitrate pentahydrate and iron nitrate nonahydrate were mixed by 1-x La x The FeO3 element chemical molar ratio is weighed, x=0.10, and then citric acid is weighed. The weighed mixture is dissolved in a mixed solvent beaker of methanol and ethylene glycol, and the volume ratio of methanol to ethylene glycol is 3:1. A magnetic stirring bar is placed in the beaker, and the beaker is placed on a constant temperature magnetic uniform table for uniform stirring. The magnetic speed is controlled, and a uniform solution is obtained after a period of time. The stirring time is 30 minutes, and the magnetic speed is 300r / min;
[0042] (2) moving the uniform solution of step (1) to a heated magnetic uniform table for stirring and heating for a period of time, the heating temperature is 100°C, the heating time is 0.5h, and the solvent evaporates to form a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a gel, the oven drying temperature is 100°C, the drying time is 24h, taking the gel out of the beaker, putting it into a pre-cleaned mortar and grinding it thoroughly, the grinding time is 0.5h, and obtaining a lanthanum-doped bismuth ferrite ceramic powder, placing the lanthanum-doped bismuth ferrite ceramic powder into a box furnace for pre-sintering treatment, the heating rate is 2°C / min, the initial sintering temperature is 500°C, the initial sintering time is 2h, the sintering conditions are normal pressure and air atmosphere, and obtaining a primary calcined powder;
[0043] (3) placing the primary calcined powder in step (2) into a circular mold and subjecting it to pressurization treatment, the pressure of the tablet press is 1-2 MPa, the pressurization time is 30 min, and a lanthanum-doped bismuth ferrite ceramic block is prepared. The obtained ceramic block is placed in a box-type furnace for calcination, the calcination temperature is 900° C., the heating time is 2 h, and the sintering conditions are normal pressure and air atmosphere, to obtain a lanthanum-doped bismuth ferrite ceramic target;
[0044] (4) Bi 0.90 La 0.10 The FeO3 target is polished with target sandpaper, and then cleaned with alcohol and dust-free paper. The LaAlO3 substrate is placed in a box furnace and sintered at 1000℃ for 2h. The sintering conditions are normal pressure and air atmosphere. Silver paste is used to fix the LaAlO3 substrate in the appropriate position of the liner. The silver paste is dried and the target is placed in the appropriate position of the target. The cavity is first vacuumed and pre-sputtered. After sputtering, a layer of La is grown first. 0.5 Sr 0.5 MnO3 bottom electrode, set the cavity infrared laser heating temperature to 700℃, after growing the bottom electrode, grow Bi 0.95 La 0.05 FeO3 film, set the cavity infrared laser heating temperature to 660℃, after growth, perform oxygen annealing, cool down to obtain Bi 0.90 La 0.10 FeO3 thin film.
[0045] The Bi prepared in this example 0.90 La 0.10 AFM morphology of FeO3 film Figure 6 As shown, it can be seen that the morphology of the film is dense island growth.
[0046] The Bi prepared in this example 0.90 La 0.10 The IV curve of FeO3 film is shown in Figure 7 As shown, it can be seen that the film has good electrical conductivity.
[0047] The Bi prepared in this example 0.90 La 0.10 The hysteresis loop and butterfly curve of FeO3 film are shown in the figure Figure 8 As shown, good hysteresis loop and butterfly curve can be seen.
[0048] In this embodiment, x=0.20, and other steps and parameters are the same as those in Embodiment 1.
[0049] The Bi prepared in this example 0.80 La 0.20 AFM morphology of FeO3 film Fig. 9 As shown, it can be seen that the morphology of the film is island-like growth.
[0050] The Bi prepared in this example 0.80 La 0.20 The IV curve of FeO3 film is shown in Fig.10 As shown, it can be seen that the film has good electrical conductivity.
[0051] The Bi prepared in this example 0.80 La 0.20 The hysteresis loop and butterfly curve of FeO3 film are shown in the figure Fig.11 As shown, good hysteresis loop and butterfly curve can be seen.
[0052] Comparative Example 2
[0053] In this embodiment, x=0.30, and other steps and parameters are the same as those in Embodiment 1.
[0054] The Bi prepared in this example 0.70 La 0.30 AFM morphology of FeO3 film Fig.12 As shown, it can be seen that the film grows smoothly.
[0055] The Bi prepared in this example 0.70 La 0.30 The IV curve of FeO3 film is shown in Fig.13 As shown, it can be seen that the film has good electrical conductivity.
[0056] The Bi prepared in this example 0.70 La 0.30 The hysteresis loop and butterfly curve of FeO3 film are shown in the figure Fig.14 As shown, good hysteresis loop and butterfly curve can be seen.
Claims
1. A method for preparing a lanthanum-doped bismuth ferrite thin film system material, characterized in that: The specific steps include: (1) Lanthanum nitrate tetrahydrate, bismuth nitrate pentahydrate and iron nitrate nonahydrate were mixed by Bi 1-x La x Weigh the chemical molar ratio of FeO3 element, then weigh citric acid, dissolve the weighed mixture in a mixed solvent beaker of methanol and ethylene glycol, put a magnetic stirrer in the beaker, put the beaker on a constant temperature magnetic uniform table for uniform stirring, control the magnetic speed, and get a uniform solution after a period of time; (2) moving the uniform solution of step (1) to a heated magnetic uniform table for stirring and heating for a period of time, and when the solvent evaporates to form a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a gel, taking the gel out of the beaker, and putting it into a pre-cleaned mortar to fully grind it to obtain a lanthanum-doped bismuth ferrite ceramic powder, and placing the lanthanum-doped bismuth ferrite ceramic powder into a box furnace for pre-sintering treatment, controlling the heating rate, initial sintering time, and sintering temperature to obtain a primary calcined powder; (3) placing the primary calcined powder in step (2) into a specific mold and subjecting it to pressure treatment to prepare a lanthanum-doped bismuth ferrite ceramic block, and placing the obtained ceramic block into a box-type furnace for calcination to obtain a lanthanum-doped bismuth ferrite ceramic target; (4) The bulk target was deposited on a LaAlO3 substrate using pulsed laser deposition to obtain Bi 1-x La x FeO3 thin film.
2. The method for preparing the lanthanum-doped bismuth ferrite thin film system material according to claim 1, characterized in that: Step (1) x=0.05-0.30, the molar ratio of citric acid to the metal cation of lanthanum-doped bismuth ferrite is 1:1, the volume ratio of methanol to ethylene glycol is 5:1-3:1, the stirring time is 30-60 minutes, and the magnetic speed is 200-400 r / min.
3. The method for preparing the lanthanum-doped bismuth ferrite thin film system material according to claim 1, characterized in that: In the step (2), the heating temperature of the mixed solution is 80-100° C., the heating time is 0.5-2 h, the oven drying temperature is 50-100° C., the drying time is 12-24 h, the grinding time is 0.5-1 h, the heating rate is 2-4° C. / min, the initial sintering temperature is 400-600° C., the initial sintering time is 2-4 h, and the sintering conditions are normal pressure and air atmosphere.
4. The method for preparing the lanthanum-doped bismuth ferrite thin film system material according to claim 1, characterized in that: In the step (3), the pressure of the tablet press is 1-2 MPa, the pressurizing time is 20-30 min, the calcining temperature is 700-900° C., the heating time is 2-12 h, and the sintering conditions are normal pressure and air atmosphere.
5. The method for preparing the lanthanum-doped bismuth ferrite thin film system material according to claim 1, characterized in that: In the step (4), the LaAlO3 substrate is fixed at a suitable position on the liner. When the vacuum degree of the chamber reaches 1×10 -4 ~2×10 -4 Pa, set the frequency of the pulse laser to 3-5Hz, the energy to 200-350mJ, first grow a bottom electrode, set the heating temperature to 600-700℃, the oxygen pressure to 10-30Pa, and grow Bi 1-x La x After the FeO3 film is grown, 1×10 4 ~5×10 4 Pa oxygen annealing, annealing time 45 ~ 60min, get Bi 1-x La x FeO3 thin film.
Citation Information
Patent Citations
Doped bismuth ferrite memristor with synaptic characteristic and preparation method thereof
CN114361337A
Bismuth ferrite film doped with lanthanide metal atoms at A site and preparation method thereof
CN115504684A
Preparation method of calcium-doped bismuth ferrite film system material
CN117144305A
Chiral lead-free ferroelectric nanostructure material as well as preparation method and application thereof
CN118598201A